Description of the Level of Digital Well-Being in Adolescents the Digital Era - Aisyatul Humayrah; Satiningsih Satiningsih (Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to examine the level of digital well‑being among adolescents aged 16–18 years in Surabaya. A total of 416 respondents from high schools, vocational schools, and Islamic schools participated in this quantitative descriptive survey. The results revealed a normal distribution of digital well‑being scores with a mean of 90 and a standard deviation of 9, indicating a stable and homogeneous pattern. Most respondents (65%) were categorized as moderate, while 15% were low and 20% high. Demographic analysis showed variations: 18‑year‑olds dominated the moderate and low categories, while 16‑year‑olds were more represented in the high category; female students tended to be in the moderate and high categories, whereas males were dominant in the low category; Grade XII students dominated the moderate and low categories, while Grade XI students were more prevalent in the high category; Surabaya Timur contributed most to the moderate and low categories, while Surabaya Selatan was more represented in the high category. In conclusion, adolescents in Surabaya generally have a moderate level of digital well‑being, with age, gender, grade level, and school region playing significant roles in shaping digital well‑being. Keywords: digital well‑being; adolescents; demographics; Surabaya; digital literacy